Opening a window in Kashmir - Guha, Ramachandra (2004)
This essay focuses on a forgotten incident in the history of India-Pakistan relations, the visit of Sheikh Abdullah to Rawalpindi and Muzaffarabad in 1964. The story is of interest to the historian, and perhaps to the policy-maker as well. Forty years down the line, the contours of the Kashmir dispute have scarcely changed at all. Now, as then, its solution must satisfy the conditions laid down in 1964 by Sheikh Abdullah: namely, that it must not lead to a sense of victory for either India or Pakistan; that it must make the minorities more secure in both countries; and that it must satisfy the aspirations of the people of Kashmir themselves. - Reproduced.
Keywords: India - Foreign relations - Pakistan; International relations